Kecurangan Akademik Dalam Perspektif Teori Fraud Diamond - Devi Maya Sofa; Endah Susilowati (STIE Mandala Jember, 2021)
Academic fraud can occur in university because it is influenced by various underlying factors, both internally and externally. The purpose of holding this study was to determine whether the pressure, opportunity, rationalization, and abilities possessed by students significantly influence the occurrence of academic fraud in university. This research was conducted on 92 students of the Accounting Major in East Java